PENINGKATAN PROMOSI PARIWISATA DESA WISATA PADANG GANTING MELALUI VIDEO PROFIL OBJEK WISATA - Komala Dewi, Ranti; Flomina G, Katrina; Khair, Ummul; Fardinal, Fardinal (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Nagari Padang Ganting is a unique village in West Sumatera, Indonesia, with a wide variety of tourist attractions, including man-made/health attractions such as hot springs, cultural attractions such as the tombs of Tuan Kadhi and Sheikh Ibrahim, and natural attractions such as Nabi's footsteps stone and the seven-tiered waterfall. However, at present, tourists only focus on visiting the hot spring tourist attraction, due to the lack of clear information about other tourist attractions in Nagari Padang Ganting. Currently, there is a website and a profile video of Nagari Padang Ganting, but it is necessary to create a profile video about the other attractions in Nagari Padang Ganting to provide more information for tourists who will visit. This activity aims to provide a solution to the existing problems, namely by creating a profile video of the Nagari Padang Ganting tourist attractions, thereby increasing the promotion of Nagari Padang Ganting tourism. This will certainly attract local and foreign tourists to visit Nagari Padang Ganting, thus helping the community's economy because it receives a multiplier effect from the tourism activities that exist in Nagari Padang Ganting. So it is directly beneficial to Nagari Padang Ganting, the Tourism Awareness Group (POKDARWIS) and the people of Nagari Padang Ganting, especially in the effort to improve community welfare through the promotion of tourist attractions in Nagari Padang Ganting. The profile video of the tourist attractions in Nagari Padang Ganting has been uploaded on the YouTube channel of the Nagari Padang Ganting Government and the Facebook social media of the Nagari Padang Ganting Government.